“Squad, sense!”: Raphael Vladmir Costa Reis - Reis, Raphael Vladmir Costa (Em Perspectiva, 2019)
The present article, an integral part of a dissertation that is under development, consists of analyzing the resonances of the civil-military coup in Sergipe, with emphasis on its sociopolitical dimension, adopting as an analytical axis the dynamics of the national conjuncture that occurred after the March of the Family of São Paulo, on March 19. In order to do so, in general terms, it is considered appropriate to understand the events that go from the precipitous actions conducted by João Goulart, through the articulations of the military conspiracy, responsible for the full realization of the institutional rupture, until the moment that refers to the "consecration" of the coup forces, represented by the realization of the "Victory March" in Carioca lands. It is based on these efforts of analysis, supported by the use of oral and printed sources, therefore, that this manuscript attempts to contribute to broaden the understanding of that arbitrary period in Sergipe.